The Age of the Crowd - Louw-Potgieter, J (PINS-Psychology in Society, 2025)
Moscovici, S. (1985). The age ot the crowd. Cambridge: Cambridge University Press. Pp. 408. ISBN: 0-521-27705-1. In his examination of ingroup ties, Freud, unlike most social psychologists, did not choose small and simple forms of groups to illustrate his ideas. Never one to avoid controversy, he proposed a brief analysis of the psychological ties within the Catholic Church and the army. It could be said that Serge Moscovici in his latest book, The age of the crowd, continues this tradition of controversy and range of explanation in social psychology.